Pengetahuan lokal dan strategi lokal Sunda dalam hadapi bencana - Samson CMS; Wina Erwina; Elnovani Lusiana (Faculty of Communication, Padjadjaran University, 2021)
The integration of community leaders with the government in all aspects of life is very important, including in the edges of various disasters. Not to mention the covid 19 pandemic, landslides, floods, tsunamis, earthquakes, erupting mountains, etc., which have not subsided. The fact that the wrong approach is always used, often the handling results in not maximum. The lack of responsive communities participating in prevention further prolongs the course of treatment. This study was conducted with the aim of finding out how local traditions, in this case the Sundanese in Tatar Karang, harmonize the community with the government in dealing with disasters. The method used is phenomenology. The results showed: 1) local knowledge about disaster mitigation; 2) obedience based on Custom, Religion and State. Conclusion: one of the local knowledge is stored in the form of certain traditions, in a community group. Only the people know where the knowledge is stored. Interested outsiders should be wise to know how each adat treats its local knowledge.